2020
DOI: 10.1371/journal.pone.0227976
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between psychosocial factors during pregnancy and preterm birth in Puerto Rico

Abstract: Psychosocial stress during pregnancy has been associated with adverse pregnancy outcomes including preterm birth (PTB). This has not been studied in Puerto Rico, an area with high PTB rates. Our objective was to develop a conceptual model describing the interrelationships between measures of psychosocial stress and depression, a result of stress, among pregnant women in Puerto Rico and to examine their associations with PTB. We used data from the Puerto Rico Testsite for Exploring Contamination Threats pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
0
10
1
Order By: Relevance
“…Another three studies included the diagnosis of mental disease as a medical status. This result is in contrast to the fact that many studies have confirmed psychosocial impacts on PTB (Eick et al, 2020; Giurgescu & Misra, 2018; Ruiz et al, 2015). It might be thought that psychological variables, such as stress, depression, and anxiety, may be difficult to evaluate as compared to the demographic and biomedical variables that are easily obtained from medical records (Nast et al, 2013).…”
Section: Discussioncontrasting
confidence: 88%
“…Another three studies included the diagnosis of mental disease as a medical status. This result is in contrast to the fact that many studies have confirmed psychosocial impacts on PTB (Eick et al, 2020; Giurgescu & Misra, 2018; Ruiz et al, 2015). It might be thought that psychological variables, such as stress, depression, and anxiety, may be difficult to evaluate as compared to the demographic and biomedical variables that are easily obtained from medical records (Nast et al, 2013).…”
Section: Discussioncontrasting
confidence: 88%
“…depression [7]. In that study, the indirect effect of stressful life events on depression through increasing perceived stress was stronger than the direct effect [7].…”
Section: Plos Onementioning
confidence: 62%
“…Studies have shown that exposure to stressors prior to or during pregnancy may increase the likelihood of adverse birth outcomes, including preterm birth and fetal growth restriction [1][2][3][4]. There are a number of stressful experiences during pregnancy that have been shown to adversely affect maternal and fetal health, including financial hardship, the death of a family member, or experiences with racial discrimination, and women are often exposed to a multitude of these stressors during pregnancy [5][6][7][8]. Certain indicators of psychosocial stress are prevalent during pregnancy, with 39% of women experiencing a stressful life event in the year prior to pregnancy [9] and estimates of depressive symptoms during pregnancy at approximately 25% [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that stress, as indicated by stressful life events, perceived stress, and depression, is higher among women who go on to deliver preterm. Furthermore, stress can be triggered from many different sources, including low socioeconomic status, elderly age, and social support ( 7 ). The maturation of hypothalamic–pituitary–adrenal axis (HPA) axis can create a pre-control hormone environment for the myometrium and enhance uterine contraction.…”
Section: Introductionmentioning
confidence: 99%